SECONDARY CONSEQUENCES OF SUBARACHNOID HEMORRHAGE IN ITS VARIOUS CAUSES (CIPEEX, 2022)
SUBARACHNOID HEMORRHAGE (HAS) IS A PATHOLOGY CONSIDERED THE THIRD MOST COMMON TYPE OF STROKE. BESIDES, IT IS FREQUENTLY ASSOCIATED WITH ANEURYSM RUPTURE. IT CAN BE CHARACTERIZED BY ABRUPT BLEEDING THAT IS DELIMITED IN THE SPACE BETWEEN THE PIA MATER AND ARACHNOID MEMBRANES. FURTHERMORE, THIS MINI SCIENTIFIC REVIEW WAS DESIGNED TO ADDRESS THE SECONDARY CONSEQUENCES OF HAS AND HOW THEY CAN CHANGE THE LIFE QUALITY OF PATIENTS AFFECTED BY THIS BLEEDING DISORDER. FOR THIS, FIVE ORIGINAL ARTICLES WERE FOUND IN PUBMED AND SCIELO DATABASES, USING THE FOLLOWING DESCRIPTORS: SUBARACHNOID HEMORRHAGE, ADULTS, PROBLEMS, DAMAGE ASSESSMENT AND SIDE EFFECTS, PUBLISHED FROM 2017, IN PORTUGUESE AND ENGLISH. THEN, IT WAS IDENTIFIED IN THE REVIEWED ARTICLES THAT THE MAIN POST-HEMORRHAGIC CONSEQUENCES OBSERVED IN THE PARTICIPANTS FROM THE STUDY WERE: NEUROCOGNITIVE DEFICIT; SYMPTOMS OF ANXIETY, DEPRESSION AND IRRITABILITY; APHASIC DISORDERS; PAIN; VASOSPASM; HYPERNATREMIA AND SEPTIC SHOCK. IN ADDITION, IT WAS ALSO NOTED THAT MOST VICTIMS OF HAS OCCUPY BEDS IN ICUS DURING THE CONDITION AND AFTER THE RUPTURE OF THE ANEURYSM. ACCORDING TO THIS, THE SELECTED ARTICLES CARRIED OUT LONG-TERM STUDIES IN ORDER TO OBSERVE THE PERSISTENCE OF ANORMALITIES AND THE POSSIBILITY OF AFFECTING THE PERFORMANCE OF DAILY ACTIVITIES. THEREFORE, IT IS CONCLUDED THAT, ALTHOUGH HAS HAS A LOW INCIDENCE AMONG INDIVIDUALS AND PROVIDES A REDUCED SAMPLE POPULATION, THE SECONDARY CONSEQUENCES AND THE DATA INDICATED IN THE ARTICLES ANALYZED CONVERGE WITH EACH OTHER.
Keywords: Subarachnoid hemorrhage; Adults; Problems; Side effect